TERRORIST PRACTICES OF ULTRA-RADICAL SALAFI IN DAGHESTAN (Case Study of the Jennet and Shari‘a Jamaats) - KURBANOV, Hanjan (CENTRAL ASIA AND THE CAUCASUS, 2006)
Very soon after the events of August 1999, the Chechen warlords changed their tactics from direct clashes with the federal forces into surprise skirmishes in the rear and subversive acts. Since the RF power structures were present everywhere in the republic and controlled all, or nearly all, of Chechnia, the terrorist “resistance forces,” which should be called “militants,” “members of illegal armed groups” or “terrorists,” stepped up their activities. “Terrorism” is understood as noninstitutional resistance, when the assets and forces of one of the sides do not allow it to acquire legal forms and oppose the enemy on the front. Certain forces in the West and certain Muslim thinkers prefer to regard the Chechen separatists as rebels, the “warriors of jihad,” “resistance fighters,” etc. For example, Yusuf al-Qaradawi, a mujtahid well known across the Arab East, distinguishes several types of terrorism: civilian or social terrorism when criminal armed groups ambush travelers on the road, use arms against them, and thus sow terror in society. The Koran is very severe with respect to them: “The punishment for those who wage war against Allah and His Apostle and strive with might and main for mischief through the land is execution, or crucifixion, or the cutting off of hands and feet from opposite sides, or exile from the land; that is their disgrace in this world, and a heavy punishment is theirs in the Hereafter” (Surah 5, ayat 33).1 The second type of terrorism is colonial terrorism existing in two variants. The first is represented by French colonialism in Algeria, where the colonialists ruled the country together with the local people. The second, says Yusuf al-Qaradawi, is represented by colonialism that strives to destroy or assimilate the local population and take their lands away from them. America is the most graphic example of this, where the Conquistadors and then the English waged wars of extermination against the local Indians and drove them into reservations. The author says: “Terrorism means the use of force and violence against innocent people, against those with whom you have no problems, with the sole aim of planting fear in others. This is what terrorism means.